Influence of Agribusiness on Tax Base Expansion in Tanzania: A Case on Cashew Production at Mtwara Region - Chindengwike, James (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2025)
This study examined the influence of agribusiness on tax base expansion in Tanzania: A case on cashew production at Mtwara Region. This study opted mixed research approach while case study used as research design of this study. The study conducted in Mtwara region, within Masasi district and Nanyumbu district. The study population was 268 TRA officers and farmer`s unions of cashew nuts. The techniques used in this study belongs to probability sampling (Simple Random Sampling) and non-probability sampling technique. Sample size for our study were 98 farmers`s unions. This study used primary and secondary data. The study was to account the significant contribution of the agribusiness on tax-base revenue growth in the economy of the country, the study conducted at TRA Masasi. The research showed that the agribusiness contributes on the national income through export, though VAT paid on each stage of production within the country and also through the employment opportunities that created to the Tanzania citizens; although the study entailed that the agribusiness does not contribute directly to the tax-revenue, since there is no any tax imposed by TRA through the government that collected from the agriculture farmers like other business entities assessed. The government through TRA should initiate the law that will impose the direct tax to the farmers in order to diversify the scope of the tax to be collected.